Emotional intelligence and conflict management styles (IR) - Nurul Ain Hidayah Abas (2010)
The research was carried out to study emotional intelligence and conflict management styles using employees in the Human Resources Division at XYZ University in Malaysia. Specifically, it aims to examine the correlation of supervisors' emotional intelligence assessed by themselves and by their subordinates. Second, this study explored if there is a relationship between emotional intelligence possessed by the supervisors and styles of handling conflict as reported by their subordinates. Three sets of surveys were used to measure the results: Emotional Quotient Index CEQI) (Self-rating), Emotional Quotient Index (EQI) (Observer) and Rahim Organisational Conflict Inventory-II (ROCI-II) Form A surveys. Results from these surveys showed that supervisors had the highest ratings on empathy but the lowest on selfregulation. Subordinates used more integrating and compromising styles when handling conflicts with their supervisors, while dominating styles were the least used. Results from multiple regression analysis showed that there were significant relationships between emotional intelligence and conflict management styles: integrating and compromising for the employees in the HR division. Interestingly, there were mixed findings between emotional intelligence ratings by the supervisors themselves and their subordinates; only one out of six supervisors gave themselves the same emotional intelligence ratings as subordinates provided.